(untitled) - The World Bank (Washington, DC, 2009)
The World Bank approaches malaria not only as a major public health issue but also as a broader development problem that costs Africa US
Keywords: Malaria,Communicable diseases,Sốt rét,Bệnh truyền nhiễm; Africa,Africa,Châu Phi,Châu Phi